Problems of primary fallopian tube cancer diagnostics during and after surgery - D.G. Sumtsov; I.Z. Gladchuk; G.O. Sumtsov; N.I. Hyriavenko; M.S. Lyndin; V.V. Sikora; V.M. Zaporozhan (Publishing House TRILIST, 2021)
To date, the reliable diagnoses primary fallopian tube cancer (PFTC) before surgery range from 0% to 10-15%. Number of misdiagnosis even during operations reaches 30-50% and PFTC is often disguised as innocent hydro-hematosalpinx or other diseases. Research objective: to study the possibilities of PFTC diagnosis during laparotomy and laparoscopy, macroscopic examination of removed macrodrugs, suboperative use of morphological studies, problems of histological interpretation of PFTC after surgery. Materials and methods. During the period from 1966 to 2020 authors of article selected and retrospectively studied quite informative medical histories of 105 patients with PFTC aged 34 to 78 years (mean age 55.8 years). All patients were operated. Revision of the pelvic organs and abdominal cavity was performed during operations. Removed macrodrugs were examined macroscopically and histologically. According to the indications during operations histological and cytological methods of rapid diagnosis were used. Immunohistochemical methods were used to interpret rare and difficult to diagnose tumors after surgery. Results. Only 7 (6.6%) from 105 patients with PFTC was not recognized during surgery, and 18 (17.1%) were diagnosed only after suboperative histological examination. Errors during operations in the initial PFTC forms (without careful study of macrodrugs and suboperative morphological examination) can reach 23.8%. Problems with the primary lession interpretation, which arose in 11 (10.5%) patients with a pronounced tumor process, did not prevent the choice of adequate surgery. The tumor dissemination of the fallopian tube outside was detected in 69 (72.4%) patients, in 25 (26.2%) among them there were lymph node metastases. Conclusion. Careful revision of the abdominal organs and macroscopic examination of removed drugs using suboperative morphological studies avoids errors in the diagnosis and surgical treatment of patients with PFTC.